2016
DOI: 10.1016/j.redox.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotection by dietary phenolics against melanogenesis induced by UVA through Nrf2-dependent antioxidant responses

Abstract: Dietary phenolics may play a protective role in UV-mediated skin pigmentation through their antioxidant and UV-absorbing actions. In this study, we investigated whether genetic silencing of Nrf2, regulating the transcription of antioxidant genes, affected melanogenesis in primary human epidermal melanocytes (HEMn) and B16F10 melanoma cells subjected to UVA (8 J/cm2) exposure. Then, we explored the antimelanogenic actions of phenolics; caffeic acid (CA) and ferulic acid (FA) providing partial UVA protection; qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
125
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(130 citation statements)
references
References 42 publications
5
125
0
Order By: Relevance
“…3) and their derivatives have been reported to display anti-tyrosinase activity. Recently, Chaiprasongsuk et al (2016) studied the anti-melanogenesis effect of dietary phenolic compounds (caffeic acid (CA), ferulic acid (FA), quercetin (QU), rutin (RU) and avobenzone (AV)) shortly after exposure of B16F10 melanoma cells to UVA radiation. Inhibition of melanin content, as well as inhibition of tyrosinase activity, was evaluated.…”
Section: Anti-tyrosinase Activitymentioning
confidence: 99%
“…3) and their derivatives have been reported to display anti-tyrosinase activity. Recently, Chaiprasongsuk et al (2016) studied the anti-melanogenesis effect of dietary phenolic compounds (caffeic acid (CA), ferulic acid (FA), quercetin (QU), rutin (RU) and avobenzone (AV)) shortly after exposure of B16F10 melanoma cells to UVA radiation. Inhibition of melanin content, as well as inhibition of tyrosinase activity, was evaluated.…”
Section: Anti-tyrosinase Activitymentioning
confidence: 99%
“…In DB-1 melanoma cells overexpressing tyrosinase, quercetin administration led to significant increase of p53 protein and the number of cells in apoptosis compared to untreated cells (8). In particular, quercetin may potentiate p53-dependent apoptosis in melanocytic cells via stimulation of nuclear factor E2-related factor 2 (Nrf2) transcriptional activity, which has been observed in various cell types including human hepatoblastoma HepG2 cells (85, 86), human BJ foreskin fibroblasts and skin HaCaT keratinocytes (87), rat DI TNC1 astrocytes (88), and UVA-irradiated mouse B16F10 melanoma cells (89). Nrf2 is a basic leucine zipper (bZIP) transcription factor that induces the expression of several genes involved in cellular redox reactions, drug metabolism and transport, energy metabolism, and intracellular iron homeostasis in response to oxidative and electrophilic stress (90).…”
Section: Transcription Of Relevant Genesmentioning
confidence: 99%
“…Quercetin has been demonstrated to induce Nrf2-mediated ARE activation in vitro in human hepatoblastoma HepG2 cells (85, 86), human BJ foreskin fibroblasts and skin HaCaT keratinocytes (87), rat DI TNC1 astrocytes (88), and UVA-irradiated mouse B16F10 melanoma cells (89). Tanigawa et al demonstrated the ability of quercetin treatment to upregulate ARE transcription by regulating both Nrf2 and Keap1 in HepG2 cells (85).…”
Section: Transcription Of Relevant Genesmentioning
confidence: 99%
See 2 more Smart Citations